KB scanning of X‐ray beam for Laue microdiffraction on accelero‐phobic samples: application to in situ mechanically loaded nanowires. (7th October 2016) - Leclere, C.; Cornelius, T. W.; Ren, Z.; Robach, O.; Micha, J.-S.; Davydok, A.; Ulrich, O.; Richter, G.; Thomas, O.
Abstract : A mapping technique has been developed where a sub‐micrometer focused polychromatic X‐ray beam is scanned across a stationary sample instead of scanning the sample in front of the X‐ray microbeam. For setups where motion is forbidden, e.g. due to the sample environment, standard methods are restricted to one singular position in the sample, whereas the new technique gives access to the complete specimen as demonstrated on an in situ mechanically deformed gold nanowire. Abstract : A mapping technique has been developed where a sub‐micrometer focused polychromatic X‐ray beam is scanned across a stationary sample instead of scanning the sample in front of the X‐ray microbeam. This method is applied to a gold nanowire during its mechanical loading using the tip of an atomic force microscope. During the loading process, such a sample is `accelero‐phobic', i.e. the sample scanning stages must not to be moved to avoid parasitic additional load. Without beam scanning, only one single position within the sample can be probed during the test. The probed material point may even change because of drifts or movements induced by the test itself. The new scanning approach facilitates the in situ mapping of the entire wire giving access to the evolution of the wire shape as well as to the boundary conditions. This novel scanning technique opens promising perspectives for studies where sample motion is forbidden because of the sample environment.